2018
DOI: 10.1038/s41598-018-20807-1
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-periodic concave microlens array for liquid refractive index sensing fabricated by femtosecond laser assisted with chemical etching

Abstract: In this study, a high-efficiency single-pulsed femtosecond laser assisted with chemical wet etching method has been proposed to obtain large-area concave microlens array (MLA). The quasi-periodic MLA consisting of about two million microlenses with tunable diameter and sag height by adjusting laser scanning speed and etching time is uniformly manufactured on fused silica and sapphire within 30 minutes. Moreover, the fabricated MLA behaves excellent optical focusing and imaging performance, which could be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 43 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…The modification acts as a seed, which expands over time. Due to the nature of the process, expanded areas form lens-like profiles and, after some time reach each other [ 197 , 198 ]. Thus, a plano concave lens array is formed with an optical grade surface finish.…”
Section: Fabrication Of Functional 3d Structuresmentioning
confidence: 99%
“…The modification acts as a seed, which expands over time. Due to the nature of the process, expanded areas form lens-like profiles and, after some time reach each other [ 197 , 198 ]. Thus, a plano concave lens array is formed with an optical grade surface finish.…”
Section: Fabrication Of Functional 3d Structuresmentioning
confidence: 99%
“… 23 Also, Zhang and co-workers employed this method to prepare a large-area concave MLA. 141 They produced about 2 million quasi-periodic MLAs with an adjustable diameter and depression height within 30 min. 141 Li et al prepared a superhydrophobic polydimethylsiloxane (PDMS) MLA by combining FLDW and FLWE ( Fig.…”
Section: Micro/nano Devices Based On 3d Structurementioning
confidence: 99%
“…Backside wet etching + thermal annealing Fused silica Hua et al [12] Ablation of microholes + wet etching Silicon Pan et al [13] Ablation of microholes + wet etching Fused silica, sapphire Zhang et al [14] Modification of photosensitive glass Foturan glass Lin et al [15] + thermal treatment, wet etching, annealing Ablation (pressure & resoldification) PDMS Yong et al [16] Ablation (pressure & resoldification) Chalcohalide glass Kadan et al [17] Two-photon polymerization Photoresist Wu et al [18] Two-photon polymerization Photoresist He et al [19] Laser ablation + CO laser polishing Fused silica Choi et al [20] Laser ablation + CO 2 laser polishing Soda-lime glass Delgado et al [21] While lens arrays are often fabricated via thermal reflow processes [22][23][24], several alternative methods such as ink-jetting [25], reactive ion etching [26] or hot embossing [27] have been demonstrated. Recently, femtosecond laser-based lens array fabrication techniques have been developed which are summarized in Table 1.…”
Section: Technology Materials Referencementioning
confidence: 99%
“…Hua et al [12] demonstrated the usage of the femtosecond laser in a backside wet etching process for geometry generation, which is followed by thermal annealing to smoothen the surface to fabricate microlens arrays in silica. Pan et al [13] and Zhang et al [14] showed the microlens array fabrication by femtosecond laser production of microholes and a subsequent wet etching step forming the lens geometry on silicon as well as silica and sapphire, respectively. Lin et al [15] modified photosensitive glass with a femtosecond laser which is further processed via thermal treatment, wet etching and annealing to fabricate the finalized optic.…”
Section: Technology Materials Referencementioning
confidence: 99%